(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Since the establishment of microbiology as a science, scientists have focused their attention on the study of pathogens of infectious diseases (morphology, cultivation methods, enzymatic properties, clarification of the range of susceptible organisms, pathogenesis of diseases caused by the pathogen, methods of diagnosis, treatment and prevention).